2020
DOI: 10.1111/ene.14251
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament‐light in former athletes: a potential biomarker of neurodegeneration and progression

Abstract: Background/Objective: This study aimed to evaluate serum neurofilament light chain (NF-L) levels in former professional contact sports athletes with multiple concussions (ExPro) as a potential biomarker of neurodegeneration and predictor of white-matter (WM) abnormality progression. Methods: Concentrations of NF-L in the serum of fifty-two cognitively normal ExPro and twenty-one healthy controls (HC) with no history of concussions were measured using single molecule array (Simoa) technology. Both groups underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 33 publications
1
18
2
Order By: Relevance
“… 13 This implies that NfL could potentially be used as a marker of ongoing neuroaxonal injury secondary to repeated concussion. 21 In our study, we did not find any difference in plasma NfL concentration between the two study groups. This may suggest that retired athletes with a history of concussions did not have a higher prevalence of neurodegenerative disease, as measured by plasma NfL or that increases in NfL related to acute brain injury may not be persistent in plasma over time.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“… 13 This implies that NfL could potentially be used as a marker of ongoing neuroaxonal injury secondary to repeated concussion. 21 In our study, we did not find any difference in plasma NfL concentration between the two study groups. This may suggest that retired athletes with a history of concussions did not have a higher prevalence of neurodegenerative disease, as measured by plasma NfL or that increases in NfL related to acute brain injury may not be persistent in plasma over time.…”
Section: Discussioncontrasting
confidence: 52%
“…13 This implies that NfL could potentially be used as a marker of ongoing neuroaxonal injury secondary to repeated concussion. 21 In our study, we did not find any difference in plasma…”
Section: Neurofilament Lightcontrasting
confidence: 49%
“…The NfL levels observed in the present study are consistent with the range of values observed in previous RSHI studies (<20 pg/ml) ( 96 98 ), including the two previous trials examining omega-3 supplementation in this population ( 38 , 39 ), indicating that even the highest values observed at the end of the season are within an expected range. To date, there have been few studies specifically examining the relationship between NfL and neuroimaging-derived white matter integrity in mTBI or RSHI vulnerable populations ( 99 102 ). These studies have identified decreased FA and increased mean diffusivity, particularly in the corpus callosum, to be associated with increased NfL ( 99 , 101 , 102 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in immunoassay technologies have enabled reliable detection of NfL in blood and have been utilized in multiple studies to demonstrate high correlation between NfL levels in CSF and blood 5 . An increased concentration of NfL in blood (serum NfL level) or CSF has been reported in numerous studies of neurodegenerative diseases 6 as well as concussion 7,8 . Since collecting blood-based biomarkers is more practical and desirable for extensive clinical trials as compared to CSF-based biomarkers, numerous studies have analyzed serum NfL levels in the context of different neurological disorders such as multiple sclerosis 9,10 , dementia 11 , progressive supranuclear palsy 12 , traumatic brain injury (TBI) 13 , Parkinson's disease 14 , Alzheimer's disease 15 , and Huntington's disease 16 .…”
mentioning
confidence: 87%